Interannual dynamics, diversity and evolution of the virome in Sclerotinia sclerotiorum from a single crop field. Issue 1 (31st March 2021) - Jia, Jichun; Fu, Yanping; Jiang, Daohong; Mu, Fan; Cheng, Jiasen; Lin, Yang; Li, Bo; Marzano, Shin-Yi Lee; Xie, Jiatao
Abstract: Mycovirus diversity is generally analyzed from isolates of fungal culture isolates at a single point in time as a snapshot. The stability of mycovirus composition within the same geographical location over time remains unclear. Not knowing how the population fluctuates in the field can be a source of unpredictability in the successful application of virocontrol. To better understand the changes over time, we monitored the interannual dynamics and abundance of mycoviruses infecting Sclerotinia sclerotiorum at a rapeseed-growing field for three years. We found that the virome in S. sclerotiorum harbors unique mycovirus compositions each year. In total, sixty-eight mycoviruses were identified, among which twenty-four were detected in all three successive years. These twenty-four mycoviruses can be classified as the members of the core virome in this S. sclerotiorum population, which show persistence and relatively high transmissibility under field conditions. Nearly two-thirds of the mycoviruses have positive-sense, single-stranded RNA genomes and were found consistently across all three years. Moreover, twenty-eight mycoviruses are newly described, including four novel, multi-segmented narnaviruses, and four unique bunyaviruses. Overall, the newly discovered mycoviruses in this study belong to as many as twenty families, into which eight were first identified in S. sclerotiorum, demonstrating evolutionarily diverse viromes. Our findings not only shed light on the annual variation of mycovirus diversity but also provide important virus evolutionary clues.